(3aQGFV GdSLGhfOis - (3eMeO Hf eMeO Hf YHO GdQTjO GdSLGhfOj GdMfaj, SQGL GdOjf CHh WGgQ,J (B598 (3g` s ((3eMeO Hf GdeajO s)
(3ChdgG (B:s
(3bGd Gdehdi GdTjN GdEeGe SQGL Gddg aGdaQGFV LeY aQjVI ai GdejQGK hEfeG LYd GdYde HgG fUa GdYde s
(3BNQgG (B:s
(3ajbSe JQcJg cPdc abO Hbi ef JQcg cd efgeG KdGKhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B233 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B106s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1247s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQGFV bhdg (B5) s
Keywords: (3Yde GdaQGFVs